(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Our body’s largest organ for infection defense is the skin. The skin can occasionally catch an infection. Numerous different types of microorganisms can cause skin infections, which can range in severity from minor to severe. Skin conditions are very common anywhere in the world. It also includes all age groups for both gender and also depends on genetic factors, different environmental conditions, the pathogen and bacterial resistance to antibiotics as a result of indiscriminate use and other risk factors as injury to the skin, obesity, diabetes and eczema disease. Gram-positive bacteria are the most common cause of bacterial skin infections, as well as viruses, fungi and parasites, as these pathogens penetrate the skin through holes, hair follicles, wounds or animal bites such as insects. They are recognized as an issue with public health in developing nations. Our review deals with the route of skin infection, microbial causes of skin infection, their pathogenesis, the most important symptoms of these infections and laboratory diagnosis methods. Conclusion: Since dermatitis is not limited to one microbial type without the other and can result from the normal flora when wounds or burns occur in the skin, serious skin infections and their symptoms vary depending on the type of microbial cause and what it secretes from toxins or other virulence factors.